Sustainable Community Health Module for Nursing Students: Supporting Vulnerable Children in Aceh - Lisa Fitriani; Afni Yan Syah; Cut Rahmiati; Juliana Juliana (Journal of Economics and Public Health, 2026)
This study aims to develop a sustainable community health module to enhance nursing students’ capacity in delivering community-based health services to vulnerable children at Rumoh Seujahtera Aneuk Nanggroe (RSAN), Aceh Besar. This study is grounded in the increasing need for effective and sustainable community health interventions for vulnerable children who often experience limited access to health education, preventive care, psychosocial support, and healthy living environments. Many children living in social welfare institutions remain at risk of poor health literacy and unmet health needs, which may negatively affect their physical, emotional, and social development. At the same time, nursing students require more structured and experiential learning opportunities to strengthen their competencies in community nursing, health promotion, and child-centered care. Despite the importance of community-based nursing education, there is still a lack of sustainable and context-specific health modules designed for vulnerable child populations in Aceh. Therefore, this research is important to bridge the gap between academic nursing training and real community health needs while supporting sustainable health services and improving the well-being of vulnerable children. A sequential mixed methods design was employed, integrating quantitative and qualitative approaches. The quantitative phase involved a survey of 70 children aged 5–18 years selected using a purposive sampling technique to assess health literacy and health-related challenges using validated instruments. The qualitative phase consisted of in-depth interviews with caregivers, nursing students, lecturers, and community health workers to explore perceptions, needs, and implementation challenges. Findings from both phases were triangulated to inform the development of a contextually relevant health module. The module was subsequently validated by experts and piloted among nursing students and children at RSAN using a pre-test and post-test design. The study is expected to produce an effective, context-based, and sustainable community health module that strengthens nursing education and community engagement.